Disposition Practices of Records in Procurement and Disposal Units of Uganda College of Commerce-Kabale. - Naturinda, Apophia (Kabale University, 2024)
The study investigated the record disposition practices in the procurement and disposal units of Uganda College of Commerce-Kabale. The study's objectives were to analyze the methods used for record disposition, identify the challenges faced during the process, and propose solutions to these challenges. Using a descriptive research design, data were collected through interviews and questionnaires. The findings revealed that the methods employed for record disposition included discarding, shredding, archiving, imaging, purging, and returning records. The challenges identified were inadequate storage facilities, delays in decision-making by administrators, insufficient storage space, and limited funds for disposing of records. Proposed solutions included adopting a records management legislative framework, training staff to equip them with the necessary expertise, ensuring consistency with policy in record disposal, avoiding unnecessary long-term storage of records, and sentencing files with reference to relevant retention schedules upon creation. The study recommended recruiting trained staff knowledgeable in disposition methods to train unskilled staff and enhance the skills of existing staff, updating retention and disposition schedules with new features and changes in retention periods, and expanding the registry and record center to provide more space for incoming and inactive records, thus eliminating congestion in storage centers.